Norbert Ksantenskiy i sv. Avgustin. K voprosu ikonografii miniatyury v rukopisi «Vita beati Norberti» iz sobraniya Bavarskoy gosudarstvennoy biblioteki/Норберт Ксантенский и св. Августин. К вопросу иконографии миниатюры в рукописи «Vita beati Norberti» из собрания Баварской государственной библиотеки - Zotova, Yelizaveta Valentinovna (Observatoriya kul'tury, 2014)
The article is devoted to the study of the only surviving illuminated manuscript of the life of Norbert of Xanten. The author analyzes the iconography of the miniature from this manuscript, compares it with miniatures and other illuminated lives of the holy archbishops, manuscripts of the works of St. Augustine, created in Germany in the same period (XII century).
Number: 6
Keywords: 👤 norbert of xanten

Ограничения в пище и дисциплина тела: практики поста в ордене регулярных каноников-премонстрантов / Ogranicheniya v pishche i distsiplina tela: praktiki posta v ordene regulyarnykh kanonikov-premonstrantov - Farré, Núria (Verbum aльманах Центра изучения средневековой культуры / Verbum alʹmanach Centra izučenija srednevekovoj kulʹtury, 2009)
Keywords: 📚 premonstratensian (general)